2021
DOI: 10.21203/rs.3.rs-331806/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Users’ Perception on Factors Contributing to Electronic Medical Records Systems Use: A Focus Group Discussion Study in Healthcare Facilities Setting in Kenya

Abstract: Background Electronic Medical Records systems (EMRs) adoption in healthcare to facilitate work processes have become common in many countries. Although EMRs are associated with quality patient care, patient safety and cost reduction, their adoption rates are comparatively low. Understanding factors associated with usage of implemented EMRs are critical for advancing successful implementations and scale-up sustainable initiatives. The aim of this study was to explore end users’ perceptions and experiences on fa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Anderson & Agarwal [8] discovered that individuals' willingness to provide access to their health information was negatively affected by concerns about privacy. On the other hand, Dinev et al [24] observed a limited correlation between attitudes towards electronic health records and concerns about privacy related to health information.…”
Section: Concerns On Privacy and Security Of Electronic Health Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson & Agarwal [8] discovered that individuals' willingness to provide access to their health information was negatively affected by concerns about privacy. On the other hand, Dinev et al [24] observed a limited correlation between attitudes towards electronic health records and concerns about privacy related to health information.…”
Section: Concerns On Privacy and Security Of Electronic Health Recordsmentioning
confidence: 99%
“…In Saudi Arabia, EMR systems were introduced in 1988 to enhance the country's healthcare system and services, aligning with the objectives set by the Saudi Ministry of Health (MOH) [7]. The MOH has prioritized the nationwide adoption of EMRs as a means to enhance the flow of patient information, reduce errors, and prevent record duplication [8]. Several successful instances of EMR adoption are evident in Saudi Arabia, with some hospitals even receiving recognition for their achievements in this area [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, EMR systems were introduced in 1988 to enhance the country's healthcare system and services, aligning with the objectives set by the Saudi Ministry of Health (MOH) [5]. The MOH has prioritized the nationwide adoption of EMRs as a means to enhance the flow of patient information, reduce errors, and prevent record duplication [6]. Several successful instances of EMR adoption are evident in Saudi Arabia, with some hospitals even receiving recognition for their achievements in this area [7].…”
Section: Introductionmentioning
confidence: 99%